Pengaruh Motivasi Belanja Hedonis, Gaya Hidup Belanja, Promosi Penjualan Terhadap Pembelian Implusif Gen Z - Sari, Putri Novita; Dadang Wiratama (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to identify the influence of the independent variables hedonic shopping motivation, shopping lifestyle, and sales promotions on the dependent variable impulse buying among Shopee consumers, especially gen z in Lamongan district. The method used is a quantitative approach by distributing questionnaires via Google Form then the test stages carried out include validity test, reliability test, multiple linear analysis test, partial t test, simultaneous F test, and coefficient of determination test (R2). The sample in this study was 100 respondents with the characteristics of generation Z, who had made purchases at Shopee, and lived in Lamongan district. The sampling method in this research used a non-probability sampling technique. Data analysis in this research utilized SPSS version 30 software as a testing tool. The research results show that hedonic shopping motivation, shopping lifestyle, and sales promotions all have a positive and significant influence on impulse buying. This is reinforced by the results of the coefficient of determination (R2) test for the independent variable of 55.9%, the remaining 44.1% is influenced by other variables outside the independent variable used in the research.